Analysis of knowledge and attitude regarding antenatal examination among nursing students in Sikkim: a descriptive co-relational study - Devi, Barkha; Khandelwal, Bidita; Das, Mridula (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The antenatal period is a time of physical and psychological preparation of birth and parenthood. Becoming a part is a time of intense learning both for parents and those close to them. This can be a time of great hope and joyful anticipation. The primary aim of antenatal care is to achieve, at the end of pregnancy, a healthy mother and healthy baby. The quality of care is more important than the quantity. Most women pass through the period with specific assessment, supportive measures and encouragement. Life threatening conditions place the woman and fetus at risk for significant mortality and morbidity. The objective of the study was to assess the knowledge of nursing students regarding the antenatal examination and also to assess their attitude towards it at selected nursing institute of Gangtok, Sikkim. Hence the present study was planned to assess and compare the knowledge and attitude towards antenatal examination among nursing students. Methods: A quantitative, descriptive, co-relational study was carried out at Sikkim Manipal College of Nursing, Vinayaka Mission College of Nursing and School of Nursing, STNM hospital Gangtok, Sikkim, India. Data were collected using structured questionnaire for which validity and reliability was ensured. 64 nursing students’ were selected through non-probability convenience sampling technique who are currently undergoing 3rd year GNM, 1st year PBBSc and 3rd and 4th year B. Sc. Nursing programme and attended regular classes on antenatal examination. Results: The findings revealed that nursing students had mean knowledge score of 20.07 (66.97%) on antenatal examination. However, the majority of nursing students (n=54, 84.3%) did not have adequate knowledge on antenatal examination. The study revealed that nursing students had positive attitudes towards antenatal examination with mean score 75.2 (89.5%) against a possible score of 84 (SD 4.098).The study also reveals that there was poorly positive relationship found between knowledge of nursing students and their attitude towards antenatal examination (P<0.05). Different nursing programme significantly influences knowledge regarding antenatal examination (???? = 0.001), while attitude was influenced by number of times nursing students performed antenatal examination and total theory hours attended respectively (P <0.05). Conclusions: A majority of nursing students demonstrated inadequate knowledge but had favorable attitude towards antenatal examination. As nurses are the major health care providers in community settings if their knowledge is enhanced it can contribute effectively to achieve the goal in reduction of maternal and infant mortality rate.